IMPLEMENTASI DIGILIB DENGAN APLIKASI KUBUKU DI DEPARTEMEN EKONOMIKA DAN BISNIS SEKOLAH VOKASI UNIVERSITAS GADJAH MADA - Umi Sugiyanti; Sunarja Sunarja; Sri Junandi (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2020)
Introduction. In the industrial revolution 4.0 libraries begin to transform their conventional services into digital libraries. The Department of Economics and Business of SV UGM is trying to add digital library services based on applications from Enam Kubuku Indonesia Company. Purpose. The research was conducted to find out the implementation of Digilib (Digital Library) with Kubuku application and its future implementation at The Department of Economics and Business of SV UGM. Method. The research used literature study method which is a stage of research carried out to search for information, theories, methods, and concepts in accordance with the problem. The information obtained is then used as a reference material to resolve problems at the research location. Literature study in this research was carried out by digging up information and references from books, online media, discussions and interviews with stakeholders, library users, and other diligib staff from Digilib UNY, ISI Yogyakarta, and I-Jogja. Results and discussion. This research resulted in an implementation of digilib using the application from Kubuku, and its future obtains very positive responses from users and leaders along with the staff. The results also produced several categories of digital libraries: bookless digilib, semi-mobile digilib, and mobile digilib. This research is expected to provide an overview of the development of digital library in the Department of Economics and Business of SV UGM and become an example for other libraries that have not yet implemented digital library.